2011
DOI: 10.4163/kjn.2011.44.6.498
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Plasma Homocysteine, Folate, Vitamin B12and Nutrient Intake and Neurocognitive Function in the Elderly

Abstract: This study examined the relationship among plasma homocysteine, folate, and vitamin B12 levels and neurocognitive function in 118 community-dwelling elderly subjects (mean age, 75.1 ± 6.7 years). The Mini-Mental State Examination (MMSE-KC) was used to screen and assess neurocognitive function in the participants. Dietary intake data including the use of dietary supplements were obtained using the 24-hour recall method by well-trained interviewers. Plasma folate and vitamin B12 concentrations were analyzed by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…van der Griend et al [ 32 ] reported that plasma folate levels were significantly lower in men than in women after an 8-week trial with 500 µg/day of folic acid. In this study, folate intake of men was significantly higher than that of women, whereas plasma folate concentration was significantly lower in men than in women, which has also been reported by other studies [ 16 33 34 ]. Therefore, men may require more folate intake to improve folate status and to reduce risk of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…van der Griend et al [ 32 ] reported that plasma folate levels were significantly lower in men than in women after an 8-week trial with 500 µg/day of folic acid. In this study, folate intake of men was significantly higher than that of women, whereas plasma folate concentration was significantly lower in men than in women, which has also been reported by other studies [ 16 33 34 ]. Therefore, men may require more folate intake to improve folate status and to reduce risk of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 90%
“…One-way ANOVA followed by Duncan's multiple range test was used determine differences in intake and plasma concentrations of folate among age groups. Pearson's partial correlation coefficient was calculated to determine possible relationships among folate intakes and plasma folate level after controlling for age, gender, body mass index, and energy intake [ 16 ]. Statistically significant differences were considered at P values < 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such circumstances around dementia continuously increase the national and socioeconomic burden. So the effective strategies for early prevention of dementia and delaying the onset of dementia are needed [ 2 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Known as folate in its natural form, folic acid belongs to the B group of vitamins, and is a very important substance in maintaining the functions of the central nervous system in human beings along with certain other B-group vitamins such as vitamin B 2 , vitamin B 6 , and vitamin B 12 (Duthie et al ., 2002) . A deficient intake of the B vitamins involved in the single-carbon metabolism can lead to the development of hyperhomocysteinemia; and an increased level of homocysteine has been reported not only to be a risk factor with regard to vascular diseases but also to cause DNA damage to the central nervous system (Kim et al ., 2011 ; Kruman et al ., 2000) . In addition to the relationship between the intake and blood level of B-group vitamins (including folic acid) and the cognitive functions, it has been also reported that a decrease in homocysteine in the blood caused by vitamin B group supplementation improved the cognitive functions (Dangour et al ., 2010 ; McMahon et al ., 2006 ; Morris et al ., 2005 ; Riggs et al ., 1996) .…”
Section: Introductionmentioning
confidence: 99%